Web-Based on-line learning (e-learning) decision support system - Firta Sari Panjaitan; Sonya Enjelina Gorat (Institute of Computer Science (IOCS), 2021)
The rapid advancement of technology has revolutionized education, paving the way for innovative learning methods such as E-Learning. However, optimizing the effectiveness of online education poses challenges in data management and decision-making processes. This research investigates the integration of Web-Based Decision Support Systems (DSS) in E-Learning to enhance learning outcomes. The study develops a mathematical formulation that quantifies the impact of DSS by considering student engagement, knowledge retention, and academic achievement. A numerical example is presented to demonstrate the application of the formulation, showcasing the positive influence of the DSS on individual students and the overall cohort. The results emphasize the potential benefits of personalized learning experiences, data-driven insights, and informed decision-making facilitated by the DSS. Nonetheless, the limitations of the study are acknowledged, warranting further research with larger and more diverse samples. Overall, this research contributes to the discourse surrounding the role of Web-Based DSS in shaping the future of online education, empowering educators and learners to unlock the full potential of E-Learning in the digital age